Factors associated with the impact of oral health-related quality of life in employees of a Peruvian university - Curo-Valdivia, Yuri Freddy (2024)
Objective: To identify factors associated with the impact of oral health-related quality of life among personnel of a Peruvian university in 2023. Materials and methods: Cross-sectional and analytical study involving 319 workers. The OHIP-14sp questionnaire was administered to assess oral health-related quality of life, and data on various sociodemographic variables, healthy habits, and use of dental services were collected. Bivariate and multivariate analysis was conducted using Chi-square and Poisson log-linear regression with robust variance, respectively. Results: 56.74% (n =181) of workers had a lower impact on oral health-related quality of life. Significant associations (p < 0.05) were found with gender, education level, and reason for dental consultation. Multivariate analysis showed that participants with higher university education had a greater negative impact compared to those with a doctorate (RPa=1,16; IC 95%: 1,04-1,28; p=0,006). Additionally, those consulting for "pain" had a greater negative impact compared to those seeking dental care for "other reasons" (RPa=1,11; IC 95%: 1,02-1,22; p=0.023). Conclusion: Education level and reason for dental consultation are associated with the impact on oral health-related quality of life among employees of a Peruvian university in 2023.